Protease-activated Receptor 4 causes Akt phosphorylation independently of PI3 kinase pathways. - Dangelmaier, Carol (Platelets, 2020)
PI-3 Kinase plays an important role in platelet activation mainly through regulation of RASA3. Akt phosphorylation is an indicator for the activity of PI3 kinase. The aim of this study is to characterize the pathways leading to Akt phosphorylation in platelets. We performed concentration response curves of LY294002, a pan-PI3 kinase inhibitor, on platelet aggregation and Akt phosphorylation, in washed human and mouse platelets. At concentrations as low as 3.12 μM, LY294002 abolished Akt phosphorylation induced by 2MeSADP and SFLLRN, but not by AYPGKF. It required much higher concentrations of LY294002 (12.5-25 μM) to abolish AYPGKF-induced Akt phosphorylation, both in wild type and P2Y12 null mouse platelets. We propose that 3.12 μM LY294002 is sufficient to inhibit PI3 kinase isoforms in platelets and higher concentrations might inhibit other pathways regulating Akt phosphorylation by AYPGKF. We conclude that Protease-activated receptor 4 (PAR4) might cause Akt phosphorylation through pathways distinctly different from those of Protease-activated receptor 1 (PAR1).